Functional delivery of lipid-conjugated siRNA by extracellular vesicles - O'Loughlin, A; Mäger, I; de Jong, O; Varela, M; Schiffelers, R; El Andaloussi, S; Wood, M; Vader, P (Elsevier, 2017)
Extracellular vesicles (EVs) are cell-derived, membranous nanoparticles that mediate intercellular communication by transferring biomolecules, including proteins and RNA, between cells. As a result of their suggested natural capability to functionally deliver RNA, EVs may be harnessed as therapeutic RNA carriers. One major limitation for their translation to therapeutic use is the lack of an efficient, robust and scalable method to load EVs with RNA molecules of interest. Here, we evaluated and optimised methods to load EVs with cholesterol conjugated small interfering RNAs (siRNAs) by systematic evaluation of the influence of several parameters, including incubation time, volume, temperature, and EV:cc-siRNA ratio. EV loading under conditions that resulted in the highest siRNA retention percentage, incubating 15 molecules of cc-siRNA per EV at 37 °C for 1 hour in 100 µl, facilitated concentration dependent silencing of HuR, a therapeutic target in cancer, in EV-treated cells. These results may accelerate the development of EV-based therapeutics.